The Structure of a Daily Food Ration of the Inhabitants Over 40 Years Old in the Republic of Kazakhstan - Roza SHAKIYEVA; Aigul ABDULDAYEVA; Kamshat AKHMETOVA; Gulnar TULESHOVA; Kulsara DOSMAMBETOVA; Nuriliya MALTABAROVA; Tatyana V. KIM; Saltanat URAZOVA; Madina GATAUOVA; Akzhunus OREKESHEVA; Altyn MOLDABAYEVA; Nazym GALIMGOZHINA; et al. (Tehran University of Medical Sciences, 2018)
The Structure of a Daily Food Ration of the Inhabitants Over 40 Years Old in the Republic of Kazakhstan